Makna Konotasi dalam Lagu “Kita Bikin Romantis” Karya MALIQ & D’Essentials - Meidivia, Sefty; Navafiitria, Azzahra Dwenka; Firmansyah, Dodi (Indo-MathEdu Intellectuals Journal, 2024)
This study focuses on the analysis of the connotative meaning contained in the lyrics of the song Kita Bikin Romantis by MALIQ & D’Essentials. Literary works, produced through language, not only reflect the life and culture of society, but also play a role in shaping and developing the culture itself. Literature as an art and science has aesthetic and analytical aspects related to the expression of emotions and ideas, including in the arts of music, drama, dance, and painting. The song Kita Bikin Romantis as a work of art uses language to convey emotional and symbolic messages, which focus on romantic actions in everyday life. This study aims to reveal how this song connects music, language, and socio-cultural contexts in creating a richer understanding of the message conveyed to the listener. Through a qualitative descriptive approach, this study explores the connotative meaning that not only shows romance through big actions, but also through small, meaningful attentions, such as serving hot tea or asking about a partner. The researcher analyzed the connotative meaning in each lyric. This study resulted in a study of the connotative meaning of a song. The results of this study are expected to contribute to the study of music semiotics and inspire listeners to better understand the interpretation of song lyrics in a broader cultural and emotional context.